IoT-Based Tracking System of Transceiver Location - Siti Aisyah; Ahmad Fauzy Daulay; Heru Wijanarko; Daniel Sutopo Pamungkas; Kamarudin Kamarudin (Jurnal Rekayasa Elektrika, 2021)
Object mapping based on location tracking methods has been widely used in various types of applications.     Most tracking systems recently use existing technology and infrastructure such as satellite, cellular and wireless (RF) technology. These existing technologies are high-cost technology that needs authorized permission to be integrated to the novel technology. This research proposed a cheap point to point device technology to track a location of a transceiver using GPS in a portable infrastructure using Line of sight radio communication. The tracking system design is connected to the IoT system in order to be more accessible. The proposed system using GPS as an identifier of the transceiver coordinate location and 433MHz radio module as media communication between transmitter and receiver. The use of a 433MHz radio frequency module which is free-license adds value to the system so that it will be easily accessed. The design of portable and internet-based devices also gives a positive value in which the system does not have to depend on existing infrastructure and the system can also be reached even if it is placed in remote areas. The system test results show that the system can be well accessed up to a distance of 6.8 km.